In-situ observation of microcrack evolution in a dual-phase steel during tensile straining. Issue 6 (12th April 2020) - Chen, Bin; Lu, Tianfeng; Yin, Kaiyang; Sun, Bingyi; Dong, Qing; Wang, Xiaodong
ABSTRACT: In this paper, the microcrack evolution in DP590 dual-phase steel was observed by in-situ straining in straining transmission electron microscopy. It was found that a void initiated ahead of a main crack. After the load was applied, a thinned area was nucleated ahead of the void tip, and it grew gradually into shallow nanovoid, penetrating nanovoid, and then new void. Meanwhile, the old void connected with the main crack. The repetitions of the procedures resulted in the continuous propagation of a crack. Interaction between microcracks was observed. The propagation direction of one microcrack may change, affected by other microcracks. Voids were observed between microcracks and have a significant effect on the coalescence of microcracks.